IMPLEMENTATION OF EDUPRENEURSHIP IN STUDENT BUSINESSES AT STUDENTS’ COOPERATIVE DARUSSALAM GONTOR MODERN BOARDING SCHOOL - Djean Andrea Kurnia; Ahmad Hilmi Al-Mujtahidi; Ahmad Nur Fajar Dwi Prakosa; Defi Firmansyah; Jaziela Huwaida (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2026)
This study aims to analyze the implementation of edupreneurship in the student cooperative of Pondok Modern Darussalam Gontor and its contribution to students’ entrepreneurial competencies, leadership skills, and character development. Although entrepreneurship education has been widely discussed in schools and universities, limited studies have explored edupreneurship practices within Islamic boarding schools (pesantren), particularly those integrating entrepreneurial learning with religious and character values. This study employed a descriptive qualitative approach using interviews, observations, and documentation as data collection techniques. Participants consisted of cooperative supervisors, student cooperative administrators, student business unit managers, and students involved in cooperative activities. Data were analyzed using an interactive model involving data reduction, data display, and conclusion drawing. The findings indicate that the student cooperative functions not only as an economic unit but also as an experiential learning laboratory where students actively engage in business management, leadership practices, decision-making, and organizational responsibilities. Through these activities, students develop entrepreneurial competencies, leadership abilities, independence, responsibility, discipline, communication skills, and teamwork. The findings also reveal that pesantren values, mentoring systems, organizational structures, and practical learning opportunities significantly support the sustainability of edupreneurship implementation. This study proposes a Value-Based Edupreneurship Model that integrates entrepreneurial competencies, leadership development, and character education within a pesantren environment. The findings contribute theoretically to edupreneurship studies and practically to the development of entrepreneurship education programs in Islamic educational institutions and other value-oriented educational settings. ABSTRAK Penelitian ini bertujuan untuk menganalisis implementasi edupreneurship pada koperasi pelajar Pondok Modern Darussalam Gontor serta kontribusinya terhadap pengembangan kompetensi kewirausahaan, keterampilan kepemimpinan, dan pembentukan karakter santri. Meskipun pendidikan kewirausahaan telah banyak dibahas di sekolah dan perguruan tinggi, penelitian mengenai praktik edupreneurship di lingkungan pesantren, khususnya yang mengintegrasikan pembelajaran kewirausahaan dengan nilai-nilai religius dan karakter, masih terbatas. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan teknik pengumpulan data berupa wawancara, observasi, dan dokumentasi. Partisipan penelitian terdiri atas pembimbing koperasi, pengurus koperasi pelajar, pengelola unit usaha santri, serta santri yang terlibat dalam kegiatan koperasi. Data dianalisis menggunakan model interaktif yang meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa koperasi pelajar tidak hanya berfungsi sebagai unit ekonomi, tetapi juga sebagai laboratorium pembelajaran berbasis pengalaman di mana santri terlibat aktif dalam pengelolaan usaha, praktik kepemimpinan, pengambilan keputusan, dan tanggung jawab organisasi. Melalui kegiatan tersebut, santri mengembangkan kompetensi kewirausahaan, kemampuan kepemimpinan, kemandirian, tanggung jawab, disiplin, kemampuan komunikasi, dan kerja sama. Hasil penelitian juga menunjukkan bahwa nilai-nilai pesantren, sistem pendampingan, struktur organisasi, dan kesempatan belajar praktis berperan penting dalam mendukung keberlanjutan implementasi edupreneurship. Penelitian ini menawarkan Model Edupreneurship Berbasis Nilai yang mengintegrasikan kompetensi kewirausahaan, pengembangan kepemimpinan, dan pendidikan karakter dalam lingkungan pesantren. Temuan penelitian ini memberikan kontribusi teoretis terhadap kajian edupreneurship serta kontribusi praktis bagi pengembangan program pendidikan kewirausahaan di lembaga pendidikan Islam dan lingkungan pendidikan berbasis nilai lainnya.